Research on Multiobjective Optimization of Bulb Tubular Turbine Based on Orthogonal Test - Jie Sun (Shock and Vibration, 2021)
The bulb tubular unit has advantages over other units in the low head, large discharge, and tidal energy. The development and utilization of low head and ultralow head hydraulic resources can increase the runner’s energy parameters, make up for the defects of large size and low speed of the unit, and reduce the construction investment. The bulb tubular turbine’s operation stability and structural strength are compared and analyzed by the orthogonal test method to improve the perfomance of bulb tubular turbine. The results show that the optimal design scheme can be obtained when the number of guide vane is 16, the distance between the guide vane and the blade is 1995 mm, the hub ratio is 0.31, the relative twist angle of the blade is 27°, and the cascade density is 0.72. After optimization, the bulb tubular turbine’s efficiency and output are increased by 5.72% and 2.86% at a low flow rate, respectively. The vortex at the tailpipe is reduced, and the blade work effect and the cavitation performance are well. The maximum pressure pulsation amplitude in the flow passage is reduced by 73.15%, the maximum blade deformation is reduced by 39.59%, and the maximum blade static stress is reduced by 13.16%. Finally, the reliability of numerical simulation results is verified by the model test.